2016
DOI: 10.5194/isprs-annals-iii-1-175-2016
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Steep Surfaces by Various Configurations of Nadir and Oblique Photogrammetry

Abstract: Commission I, ICWG I/VbKEY WORDS: Photogrammetry, UAS, Sandpit, Point Cloud, Analysis, Assessment ABSTRACT:Among the parts of the territory requiring periodical and careful monitoring, many have steep surfaces: quarries, river basins, landslides, dangerous mountainsides. Aerial photogrammetry based on lightweight unmanned aircraft systems (UAS) is rapidly becoming the tool of election to survey limited areas of land with a high level of detail. Aerial photogrammetry is traditionally based on vertical images an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, it was also demonstrated that nadir orientation images along with a dense distribution of ground control points (GCPs) exhibited similar accuracy, which is even comparable to the one obtained from a terrestrial laser scanner [21]. In addition, various datasets including different configurations of nadir-oblique imagery were evaluated in terms of point cloud density and accuracy and showed no significant differences [22]. Nadir and off-nadir images were evaluated for high-resolution topography, presenting an accuracy of a few centimeters [23].…”
Section: Introductionmentioning
confidence: 76%
“…However, it was also demonstrated that nadir orientation images along with a dense distribution of ground control points (GCPs) exhibited similar accuracy, which is even comparable to the one obtained from a terrestrial laser scanner [21]. In addition, various datasets including different configurations of nadir-oblique imagery were evaluated in terms of point cloud density and accuracy and showed no significant differences [22]. Nadir and off-nadir images were evaluated for high-resolution topography, presenting an accuracy of a few centimeters [23].…”
Section: Introductionmentioning
confidence: 76%
“…1) Steep Surfaces: Regularly monitoring the boundaries of a territory including steep surfaces, e.g. mountainsides, quarries, landslides or river basins, is amongst the important applications of aerial photogrammetry, which can be achieved with a decent level of details using lightweight UASs, having recently led to higher-quality results taking advantage of inclined images under oblique photogrammetry frameworks, rather than relying on strictly vertical images [74]. In the latter study, a large sandpit has been considered as a casestudy, with linear, radial and semi-circular strips as different flight configurations, where 300 control points were captured using a topographic TS.…”
Section: E Street-level Modelingmentioning
confidence: 99%
“…Chudley et al [19] called "Highaccuracy UAV photogrammetry of ice sheet dynamics with no ground control points", the application of an alternative SFM-MVS (structure from motion-multi-view stereo) geolocation method called GNSS-supported aerial triangulation was presented; in this method, a carrier-phase GNSS receiver located onboard georeferences the SFM-MVS point cloud, significantly reducing the need for GCPs. Considering various flight configurations such as linear strips, radial strips and curved strips, the diverse obtained datasets were evaluated in terms of the density of the extracted point clouds and the distance between the reconstructed surface and control points [20].…”
Section: Introductionmentioning
confidence: 99%